Treatment of Posttraumatic Cubitus Varus With Corrective Supracondylar Humeral Osteotomies Using the Methyl Methacrylate External Fixator - Acar, Mehmet A.; YILDIRIM, Serhat; Elmadag, NUH MEHMET; ELMADAĞ, NUH MEHMET; Senaran, Hakan; OGUN, Tunc C. (My University, 2014)
Background: In upper and lower extremity fractures and osteotomy fixation, the use of methyl methacrylate (MM) as an external fixator presents an alternative method. The primary aim of this retrospective study was to evaluate the midterm outcome of pediatric patients who underwent corrective humeral supracondylar lateral closing-wedge osteotomy, with the external fixation system composed of MM and multiplane K-wires. Methods: Fourteen consecutive cases with cubitus varus, who underwent corrective osteotomy with a limited lateral approach stabilized with MM and the multiplane K-wires external fixator system between January 2006 and May 2010, were retrospectively evaluated. Time of union, preoperative and postoperative elbow range of motion, and humeroulnar angle were measured. Results were rated as excellent, good, or poor, according to Bellemore criteria. Results: There were a total of 6 female patients and 8 male patients with a mean age of 5.7 years (range, 3 to 9 y). The mean follow-up period was 28.2 months (range, 24 to 48 mo). The mean humeroulnar angle was (-) 18.6 degrees preoperatively, and (+) 16.3 degrees at the final follow-up. Thirteen patients were evaluated as excellent and 1 patient as good, according to Bellemore criteria. Union was seen in all patients at mean 7 weeks (range, 6 to 8 wk). Pin tract infection was observed in 1 patient and treated with oral antibiotics. Loss of correction was not observed in any patient during follow-up. Conclusions: External fixation of corrective supracondylar humeral osteotomy with MM and multiplane K-wires is a practical, effective, reliable, and cheap alternative method that can be applied. Level of Evidence: Level IV. Retrospective study.